Behovet for store ordbøker i en samlet norsk ordbokpolitikk - Vonen, Arnfinn Muruvik (LexicoNordica, 2016)
In this article, the concept of ‘large scientific dictionary’ is approached, and two Norwegian projects are presented and discussed – one almost completed, the other still at the planning stage. All kinds of dictionaries make up an important part of the total writtenlanguage infrastructure of a language community. Large scholarly dictionaries represent fundamental documentation of a language and often function as works of source and reference for smaller dictionaries. One current and one planned large scholarly dictionary project of Norwegian are presented and discussed: Norsk Ordbok 2014 (‘Norwegian Dictionary 2014’), covering Norwegian spoken dialects and the Nynorsk written tradition, and Bokmålets og riksmålets ordbokverk (‘The Dictionary of Bokmål and Riksmål’), covering that segment of written Norwegian that is not Nynorsk.